Applying Ontological Similarity to Automatic Service Composition to Generate Alternative Business Processes - Viana, Phillip Luiz; Becerra, Jorge Luis Risco (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
With the growing trend towards increased use of mobile technologies, companies have been providing their services on the web more than ever in order to fulfill user requests quickly in various situations. It is often necessary that two or more services from different providers are automatically composed in order to meet a single user request during runtime: this is called automatic composition of services. When a service composition is executed, it is automating a business process associated to the user request. If no compositions are found that can fulfill the request, the user might want to relax his requirements to accomplish his goal alternatively. The objective of this work is to present an automatic composition model that uses similarity between concepts of an ontology to generate alternative service compositions, thus enabling a single user request to be met in several different ways through different business processes. The proposal is validated through a software prototype that is exercised in the tourism domain.